The alignment of ultrasonic root-end cavity preparations using an in situ cadaver model - Abdullah Ali Al-Sharif; Essam Abdullah Almanea; Ibrahim Ali Ahmad (Wolters Kluwer Medknow Publications, 2018)
Aim: This study aims to compare the alignment of root-end cavities prepared with ultrasonic tips with the root canal outline in teeth with and without root canal fillings using an in situ cadaver model. Materials and Methods: Twenty-eight bilaterally matched pairs of human teeth from five cadavers were equally divided into two groups: teeth with root canal fillings (RCF) and teeth without root canal fillings (NRCF). The resected root surface was stained with methylene blue and examined under magnifying loops; then, the root-end cavities were prepared in both groups using ultrasonic tips and filled with amalgam. The teeth were carefully extracted, mounted in resin blocks, radiographed from two angles, and then sectioned at 3 mm from the root end. The alignment of root-end cavities in both groups was compared using defined criteria. Results: The RCF group had a significantly higher incidence of centered root-end preparations than NRCF group on the buccolingual (79% vs. 64%) and mesiodistal (64% vs. 24%) directions. However, both groups showed high incidence of deviated cavities at the horizontal cross-section and the difference between them was not significant. Conclusions: The presence of root canal filling improved the alignment of root-end cavities prepared with ultrasonic tips.